Self-Report Passion in Students: An Attempt to Measure - Byra, Stanisława; Oszwa, Urszula; Buczak, Agnieszka; Łukasik, Izabella Maria (Przegląd Badań Edukacyjnych (Educational Studies Review), 2025)
The paper focuses on measuring the subjective perception of passion and its main characteristics in university students. The article presents an innovative tool for measuring the subjective perception of passion and its main characteristics in university students. It proposes a tool – Self-Report Passion Inventory (SRPI). SRPI is based on the definition of passion as strong inclination toward an activity that people like (or even love), that they find important, and in which they invest considerable time and Energy. The tool includes two parts, the first one is used to qualitatively characterize the subject’s passionate activity, the second one is used to analyze passion in three dimensions: personal benefits of passion, origin of passion, balancing passion with life. The obtained results are promising, although they also revealed weaknesses of the proposed measurement. It is necessary to continue research and more advanced analyses, mainly checking the stability and validity of this tool.